StudentLink. A generic calendar platform - Andreassen, Ruben Alexander (UiT Norges arktiske universitet, 2015)
Large organizations often use many software applications. In some cases, two or more of these applications contains information that is very similar or the same. In this thesis we are going to look at calendar information. UiT - The Arctic University of Norway is a large organization which uses many applications that contains calendar information. Fronter, Syllabus and Microsoft Exchange all covers different needs of the organization, but it is challenging to get a fast and easy overview of calendars from several of the systems at the same time. By creating a generic calendar platform that communicates with these systems, we get a new combined calendar system that contains every calendar within the organization. This platform implements many interfaces to suit the needs of an end user or end user application. The result is that the end user gets everything in one place, without the need to access several different portals and manually compare calendars. The generic calendar platform is also easily extensible, meaning that it could reach outside the organization.